The relationship between Competitive Strategy Drivers and Performance of manufacturing Small and Medium Enterprises in Nairobi County, Kenya - Baariu, Victor Laibuni; Gathungu, James; Ndemo, Bitange (European Scientific Journal, ESJ, 2021)
This study determines the influence of competitive strategy drivers on the performance of manufacturing SMEs in Nairobi County in Kenya. Small and medium enterprises (SMEs) are the backbone of many economies all over the world through creation of employment opportunities as well as wealth creation for entrepreneurs. Strong competitive strategy drivers offer advantage to SMEs to help them achieve good performance and remain competitive in their respective markets. The study was anchored on resource-based theory which provided a framework for examining the association between the research variables. For the methodology, a cross-sectional survey was done covering 334 manufacturing small and medium enterprises in Nairobi County, Kenya. Structured questionnaires were used for data collection with a response rate of 89.6%. Various descriptive statistics were used to project the demographic characteristics of the association and the respondents. Inferential statistics was used to assess up the connection between the factors and test the model. The results indicated that the three competitive strategy drivers of environmental based drivers, resource-based drivers and hybrid strategy drivers exhibited significant relationship with performance of the Manufacturing SMEs in Nairobi county. The study’s recommendations will be useful to management of manufacturing-sector SMEs in developing long term strategies to address constraints that could have led to low capacity utilization and productivity in the sector. Additionally, it may be used to guide policy formulations geared to support manufacturing SMEs operations. The researcher recommends similar research to be undertaken in other SMEs and also have more managers respond to the questionnaires in order to enrich the collected data.